Polyethylenimine Modified and Non-Modified Polymeric Micelles Used for Nasal Administration of Carvedilol - Kahraman, Emine; Karagoz, Ayse; Dincer, Sevil; Ozsoy, Yildiz (AMER SCIENTIFIC PUBLISHERS, 2015)
This study evaluates the ability of polyethylenimine-modified and non-modified polymeric micelles to enhance permeation through the nasal mucosa for a highly hydrophobic model drug. Carvedilol was loaded into polyethylenimine-modified and non-modified micelles by direct dissolution. Formulations were characterised by critical micelle concentration, micelle particle size and distribution, zeta potential, morphological structure and entrapment efficiency. The drug entrapment efficiency was determined to be as high as 77.14%, while micelle particle sizes and zeta potentials were within the range of 140.0-279.9 nm and (-40.6)-(+25.9) mV, respectively. In vitro studies showed 100% release of carvedilol from micelles in 120 hours. Ex vivo permeation studies showed that the drug in polyethylenimine non-modified micelles passed more efficiently than the drug in polyethylenimine modified micelles. These results demonstrated that polyethylenimine modified micelles did not significantly affect the permeation of the drug when compared to polyethylenimine non-modified micelles. On the contrary, the drug in poly(L-lactide)-block-methoxy poly(ethylene glycol) 5000 micelles, the polyethylenimine non-modified micelles, showed the highest permeation rate through bovine nasal mucosa. In conclusion, poly(L-lactide)-block-methoxy poly(ethylene glycol) 5000 polymeric micelles maybe useful as novel drug carriers that increase the permeation through the nasal mucosa.
Keywords: Polymeric Micelle; Nasal Permeation; Polyethylenimine (PEI); Poly(L-lactide)-Block-Methoxy Poly(ethylene glycol)5000 (PLL-b-mPEG5000) Micelles; Carvedilol; BLOCK-COPOLYMER MICELLES; METHOXY POLY(ETHYLENE GLYCOL); IN-VITRO; DRUG; DELIVERY; INDOMETHACIN; Science & Technology - Other Topics; Materials Science